2013
DOI: 10.3390/ijms14022980
|View full text |Cite
|
Sign up to set email alerts
|

Compound K, a Ginsenoside Metabolite, Inhibits Colon Cancer Growth via Multiple Pathways Including p53-p21 Interactions

Abstract: Compound K (20-O-beta-d-glucopyranosyl-20(S)-protopanaxadiol, CK), an intestinal bacterial metabolite of ginseng protopanaxadiol saponins, has been shown to inhibit cell growth in a variety of cancers. However, the mechanisms are not completely understood, especially in colorectal cancer (CRC). A xenograft tumor model was used first to examine the anti-CRC effect of CK in vivo. Then, multiple in vitro assays were applied to investigate the anticancer effects of CK including antiproliferation, apoptosis and cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
69
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 80 publications
(71 citation statements)
references
References 46 publications
2
69
0
Order By: Relevance
“…The expression of cyclin E2 peaks at the G1-S phase and exhibits a pattern of tissue specificity distinct from that of cyclin E1 (34, 35). In addition, although not involved in top 20 upregulated gene list, CDKN1A (p21) was significantly upregulated by the treatment of PPD, which is consistent with previous reports that PPD analogs increased p21 expression in protein level (36, 37). The p21 binds to all G1/S cyclin-cdk complexes, in preventing the G1-S transition, leading to G1 arrest and inhibiting cell proliferation (38).…”
Section: Discussionsupporting
confidence: 91%
“…The expression of cyclin E2 peaks at the G1-S phase and exhibits a pattern of tissue specificity distinct from that of cyclin E1 (34, 35). In addition, although not involved in top 20 upregulated gene list, CDKN1A (p21) was significantly upregulated by the treatment of PPD, which is consistent with previous reports that PPD analogs increased p21 expression in protein level (36, 37). The p21 binds to all G1/S cyclin-cdk complexes, in preventing the G1-S transition, leading to G1 arrest and inhibiting cell proliferation (38).…”
Section: Discussionsupporting
confidence: 91%
“…Our previous research data showed that compound K is a primary metabolite of American ginseng root [21]. A narrow mass window of 0.01 Da to restructure the EICs of ginsenoside Rb 1 and compound K of the typical plasma sample is shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Most ginsenosides are converted to their metabolites in the gastrointestinal tract. Many studies have reported similar or superior effects of metabolites in comparison to their parent ginsenosides [6,34,69]. Further studies and deeper insights into the interactions between ginsenoside compounds and their metabolites with cellular targets will facilitate the development of novel medicinal and cosmeceutical products.…”
Section: Resultsmentioning
confidence: 96%
“…Indeed, various studies have outlined its biological activity and underlying mechanisms of action [16,28,59,65]. The anticancer activity of compound K has been studied for several decades [29,63,69]. In a colon cancer model, compound K induced both apoptotic and autophagic pathways via ROS generation and c-Jun NH2-terminal kinase activation [29].…”
Section: Biological Activitiesmentioning
confidence: 99%